2019
DOI: 10.1111/gcb.14560
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term dietary shift and population decline of a pelagic seabird—A health check on the tropical Atlantic?

Abstract: In the face of accelerating ecological change to the world's oceans, seabirds are some of the best bio‐indicators of marine ecosystem function. However, unravelling ecological changes that pre‐date modern monitoring programmes remains challenging. Using stable isotope analysis of feathers and regurgitants collected from sooty terns (Onychoprion fuscatus) nesting at a major Atlantic colony, we reconstructed a long‐term dietary time series from 1890 to the present day and show that a significant dietary shift oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…Likewise, it has been suggested that hydrodynamic forces around hard structures could modify prey availability, thereby increasing a seabird’s rate of energy acquisition 51 . While our findings suggest that terns exploit the flood wake of a device, an overall ecological (population-level) benefit through increased individual energy acquisition can only be determined when accounting for parameters relating to, e.g., foraging success, prey profitability, and breeding performance 51,52 .…”
Section: Discussionmentioning
confidence: 85%
“…Likewise, it has been suggested that hydrodynamic forces around hard structures could modify prey availability, thereby increasing a seabird’s rate of energy acquisition 51 . While our findings suggest that terns exploit the flood wake of a device, an overall ecological (population-level) benefit through increased individual energy acquisition can only be determined when accounting for parameters relating to, e.g., foraging success, prey profitability, and breeding performance 51,52 .…”
Section: Discussionmentioning
confidence: 85%
“…(a co-author of this paper) at the University of Birmingham and since then they have published 16 peer-reviewed scientific papers and a book (e.g. Bolton et al, 2012 ; Reynolds et al, 2019 ). Working closely also with the Ascension Island Government and the University of Exeter (Cornwall Campus) in the UK, they have also provided invaluable seabird tracking data towards the August 2019 designation of the largest marine protected area (MPA) in the entire Atlantic and taken ownership of the Biodiversity Action Plan (BAP) on the island, providing a Species Action Plan (SAP) for the sooty tern ( Onychoprion fuscatus ) and the brown noddy ( Anous stolidus ).…”
Section: Regulation Of Wildlife-focussed Citizen Science: the Key Soumentioning
confidence: 99%
“…Impacts are not only observed directly on their prey but can produce cascading effects on other marine species and communities. For example, the increase in tuna fishing activity in the 1960's in the eastern tropical Atlantic Ocean and the consequent decline of tuna populations in that area is thought to have caused a shift in the diet and a dramatic decline of the once massive Sooty tern Onychoprion fuscatus population of Ascension island which depends on interactions with sub-surface predators to locate and catch prey (Reynolds et al, 2019).…”
Section: Introductionmentioning
confidence: 99%